2012
DOI: 10.1111/head.12013
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative MRI Studies of Chronic Brain White Matter Hyperintensities in Migraine Patients

Abstract: The MRI measurements denote tissue damage with axonal loss, low glial cell density, and an enlarged extracellular space with an increased extracellular water fraction. These radiological features might be the consequences of microvascular ischemic changes during migraine attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 47 publications
6
22
0
3
Order By: Relevance
“…If the nature of WMHs is ischemic, different types of vascular mechanisms and differences in the degree of tissue damage may explain these processes. In our previous and present study, the 1 H‐MRS measurements presented axonal damage with mitochondrial impairment within the hyperintensity. In the animal model of multiple sclerosis, spontaneously reversible inflammatory axon damage with intra‐axonal mitochondrium pathology was discovered .…”
Section: Discussionsupporting
confidence: 69%
“…If the nature of WMHs is ischemic, different types of vascular mechanisms and differences in the degree of tissue damage may explain these processes. In our previous and present study, the 1 H‐MRS measurements presented axonal damage with mitochondrial impairment within the hyperintensity. In the animal model of multiple sclerosis, spontaneously reversible inflammatory axon damage with intra‐axonal mitochondrium pathology was discovered .…”
Section: Discussionsupporting
confidence: 69%
“…Our findings are particularly interesting in this population, 23,24 since thalamocortical network dysfunction, 25,26 thalamic microstructural changes, 27,28 and thalamic morphological abnormalities 29 have been recently demonstrated in individuals with migraine. Migraine is a disorder that is frequently clinically and radiographically mistaken for MS, 5,6 and previous studies have also suggested an increased risk of migraine in patients with MS. 30 In our MS + c cohort, 6/10 participants had migraine.…”
Section: Discussionmentioning
confidence: 63%
“…White matter lesions were detected more often in migraine patients than healthy controls [17,18] and found to be associated with frequency of attacks, age and family history of migraine [18] as well as disease duration [19,20]. Microvascular ischemic disturbances are suggested as a cause for alterations of white matter microstructure [21].…”
Section: White Matter Abnormalities In Migrainementioning
confidence: 98%